Quetiapine Excretion Into Human Breast Milk. Issue 4 (August 2018) - Yazdani-Brojeni, Parvaneh; Tanoshima, Reo; Taguchi, Nobuko; Garcia-Bournissen, Facundo; Wallach, Izhar; Moretti, Myla E.; Verjee, Zulfikarali; Ito, Shinya
Abstract: Background: Risk assessment of the use of quetiapine during breastfeeding is challenging owing to a paucity of data. Methods: A pharmacokinetic study was conducted in lactating women who were taking quetiapine. The primary endpoint was to determine quetiapine concentration profiles in milk and estimated infant exposure levels. Multiple milk and a single blood quetiapine concentrations were determined using a highly sensitive liquid chromatography with tandem mass spectroscopy method. Results: Nine subjects receiving fast-release quetiapine (mean dose, 41 mg/d) were analyzed at steady state. The mean milk/plasma drug concentration ratio at 2-hour postdose was 0.47 (SD, 0.50; range, 0.13–1.67). The mean milk concentration of each patient was 5.7 ng/mL (SD, 4.5; range, 1.4–13.9 ng/mL). The mean infant quetiapine dose via milk per body weight relative to weight-adjusted maternal dose was 0.16 % (SD, 0.08; range, 0.04%–0.35%). Conclusions: Infant exposure levels to quetiapine via milk are predicted to be very small.